2010
DOI: 10.1111/j.1744-7429.2010.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics of the Endemic Mexican Heliconia uxpanapensis in the Los Tuxtlas Tropical Rain Forest

Abstract: Heliconia uxpanapensis (Heliconiaceae) is an outcrossing endemic herb that grows within continuous and fragmented areas of the tropical rain forest of southeast Veracrúz (México). The genetic diversity, population differentiation, and genetic structure of seven populations of the studied species were assessed using inter-simple sequence repeat) markers. Population differentiation was moderately high (F ST range: 0.18-0.22) and indirect estimates of gene flow were rather low (Nm = 0.65-0.83). Analysis of molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
3
14
0
2
Order By: Relevance
“…Most genetic variation is contained among individuals within populations (96%) rather than between populations (3%) in fragments of different size. A similar result was obtained for other understory tropical herbs in the same region (Cuartas-Hernández & Núñez-Farfán, 2006; Suárez-Montes, Fornoni & Núñez-Farfán, 2011). Genetic clustering analyses revealed that most populations shared genetic information of one cluster or community, which explain the low genetic differentiation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Most genetic variation is contained among individuals within populations (96%) rather than between populations (3%) in fragments of different size. A similar result was obtained for other understory tropical herbs in the same region (Cuartas-Hernández & Núñez-Farfán, 2006; Suárez-Montes, Fornoni & Núñez-Farfán, 2011). Genetic clustering analyses revealed that most populations shared genetic information of one cluster or community, which explain the low genetic differentiation.…”
Section: Discussionsupporting
confidence: 85%
“…The impact of rainforest fragmentation on the genetic structure of plant populations is highly variable, depending on life history, life-span, and mating system (Cuartas-Hernández & Núñez-Farfán, 2006; Figueroa-Esquivel et al, 2010; Suárez-Montes, Fornoni & Núñez-Farfán, 2011; Chávez-Pesqueira et al, 2014). At the landscape scale, factors like the spatial configuration of fragments can also explain the genetic change of populations (Leimu et al, 2006; Vranckx et al, 2011; Aparicio et al, 2012; Chávez-Pesqueira et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The program Peakmatcher ( DeHaan et al, 2002 ) was used to generate 0/1 matrices of banding patterns. Bands occurring in fewer than 5% (or more than 95%) of accessions within a species were discarded ( Lynch and Milligan, 1994 ;Suárez-Montes et al, 2011 ;Martínez-Natarén et al, 2014 ). AFLP bands were assumed to correspond to loci with two alleles, in which band presence indicated either a dominant homozygote or a heterozygote, while band absence indicated a recessive homozygote.…”
Section: Resultsmentioning
confidence: 99%
“…The impact of rainforest fragmentation on genetic structure is highly variable between species depending on life history, life-span, and mating system (Cuartas-Hernández & Núñez-Farfán, 2006;Figueroa-Esquivel et al, 2010;Suárez-Montes, Fornoni & Núñez-Farfán, 2011;Chávez-Pesqueira et al, 2014). At the landscape scale, factors like spatial configuration of fragments can also explain the genetic change of populations (Leimu et al, 2006;Vranckx et al, 2011;Aparicio et al, 2012;Chávez-Pesqueira et al, 2014).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%